Effects of egg phosvitin on mucosal transcriptional profiles and luminal microbiota composition in murine colon. Issue 5 (3rd May 2019) - Li, Mei; Zhang, Qinjun; Wang, Ruihan; Lu, Mei; Xu, Xueming; Liu, Xuebo; Duan, Xiang
Abstract : The effects of egg phosvitin on epithelial gene expression, abundance of bacteria in colon and their correlation have been explored. Abstract : Egg phosvitin has been traditionally considered as a nutritionally negative protein for its low digestibility in the gastrointestinal tract. Whether it could exert nutritional functions in the large intestine is not known. In this work, the influence of phosvitin on luminal microbiota composition and mucosal transcriptome was investigated with young (3-week) and adult (8-week) mouse models. In young groups, phosvitin mainly suppressed genes related to lipid metabolism, whereas the regulated genes in adult individuals encompassed various biological processes, such as carbohydrate metabolism, sigestive system and others. Phosvitin increased the proportion of Bifidobacterium in the young group, and reduced amounts of pathogenic microbes in the adult group, including Helicobacter and Mucispirillum . There was a close relationship between gene expression changes and abundance of bacteria. Finally, phosvitin reduced the ammonia concentrations in feces for both young and adult groups. These findings suggested that phosvitin modified the large intestinal ecosystem, exhibiting potentially beneficial effects on gut health.